Psychological Flexibility and its Relationship to Life Satisfaction among University Students: A Field Study on Clinical Psychology Master's Students at Ghardaia University (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:      The Following Study Aims To Reveal The Relationship Between Psychological Resilience And Life Satisfaction Among University Students. For This Purpose, The Descriptive Approach Was Adopted, And The Two Scales Of Psychological Resilience And Life Satisfaction Were Used, Which Were Applied To A Sample Of 45 Students. After Processing The Data Statistically, We Reached A Set Of Results, The Most Important Of Which Are:- There Is A Statistically Significant Relationship Between Psychological Resilience And Life Satisfaction Among Clinical Psychology Master's Students.- There Are No Differences In The Level Of Psychological Flexibility And In The Level Of Life Satisfaction Due To The Gender Variable.Keywords: Positive Psychology, Psychological Flexibility, Life Satisfaction Clinical Psychology, University Education.